Risks and benefits of direct oral anticoagulants versus warfarin in a real world setting: cohort study in primary care - Vinogradova, Yana; Coupland, Carol; Hill, Trevor; Hippisley-Cox, Julia (BMJ Publishing Group, 2018)
Objective: To investigate the associations between direct oral anticoagulants (DOACs) and risks of bleeding, ischaemic stroke, venous thromboembolism, and all cause mortality compared with warfarin.